Selective electrochemical determination of sucrose in sugarcane juice using a reduced graphene oxide modified electrode functionalized with a molecularly imprinted aspartic acid electropolymerized film - de Prinsipe, Gabrieli Corrêa [UNESP]; Falone, Max Fabrício [UNESP]; Buffon, Edervaldo [UNESP]; Barbiéri, André Lucas [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier, 2025)
This study presents a novel electrochemical sensor developed for the highly selective and ultrasensitive detection of sucrose (SUC). The fabrication of the electrochemical sensor involves the electropolymerization of a molecularly imprinted poly(aspartic acid) film onto a nanostructured surface modified with reduced graphene oxide (GCE/rGO@pAA). Electrochemical, microscopic, and spectroscopic analyses were performed, confirming the effectiveness of the surface modification steps. After the optimization of experimental conditions, analytical curves were obtained within the linear concentration range of 1.0 × 10⁻¹⁴ to 1.0 × 10⁻¹² mol L⁻¹, showing a limit of detection, limit of quantification, and amperometric sensitivity of 2.7 × 10⁻¹⁵ mol L-1, 8.1 × 10⁻¹⁵mol L-1 and 3.6 × 107A L mol -1, respectively. Selectivity assays indicated that the GCE/rGO@pAA sensor exhibits excellent performance in the selective recognition of sucrose. The proposed analytical method was effectively applied to sugarcane juice samples, achieving recovery rates between 102 % and 112 % (RSD ≤ 5 %), indicating its accuracy in complex matrices such as sugarcane juice.